Sonotope patterns within a mountain beech forest of Northern Italy: a methodological and empirical approach - Farina, Almo; Mullet, Timothy C. (Frontiers in Ecology and Evolution, 2024)
According to the Sonotope Hypothesis, the heterogenous nature of the acoustically sensed, but not yet interpreted, environmental sounds (i.e., sonoscape) is created by the spatial and temporal conformation of sonic patches (sonotopes) as recently been described in a Mediterranean rural landscape. We investigated the Sonotope Hypothesis in a mountain beech forest of the Northern Apennines, Italy that is notoriously poor in soniferous species. Our aim was to test whether sonotopes were temporally distinct over seasonal and astronomical timeframes and spatially configured in relation to vegetation variables. We used the Acoustic Complexity Index (ACItf) to analyze the heterogeneity of sonic information gathered from an array of 11 sound recorders deployed within a lattice of eleven 4-ha hexagonal sample sites distributed throughout a 48-ha managed beech forest. We visualized and described the temporal patterns of ACItf between seasons (May–June and July–August 2021), across six astronomical periods (Night I, Morning Twilight, Morning, Afternoon, Evening Twilight, and Night II), and according to two aggregated frequency classes (≤2000 and >2000 Hz). We introduced Spectral Sonic Signature (SSS) calculated from the sequence of ACItf values along frequency bins as a descriptor of the dynamic production of sounds across spatial and temporal scales. We calculated Mean Spectral Dissimilarity to compare SSS values across temporal periods and between sample sites. We identified sonotopes by grouping similar SSS for each sample site generated from cluster analyses and visualized their spatial arrangements. Frequencies ≤2000 Hz (mainly geophonies from wind and rain) were more prevalent than frequencies >2000 Hz (mainly biophonies from songbirds). Despite there being no strong relationship to vegetation variables and minimal biophony and anthropophony, distinct sonotopes still emerged for every astronomical and seasonal period. This suggests that the sonoscape expresses distinct spatial and temporal sonotope configurations associated with the temporal and spatial patterns of geophysical events that generate geophonies with minimal animal or anthropogenic occurrences. A new strategy based on the reintroduction of indigenous trees and shrubs in managed clearings should be considered for enhancing local biodiversity conservation along with ecoacoustic monitoring based on the Sonotope Hypothesis.